Solubility and density of egg white proteins: effect of pH and saline concentration - Machado, Flávia Ferreira; Coimbra, Jane S. R.; Rojas, Edwin E. Garcia; Minim, Luis A.; Oliveira, Fabı́ola C.; Sousa, Rita de Cássia S. (LWT - Food Science and Technology, 2007)
Influence of different pH values (3.0, 4.6, 6.0, 8.0 and 9.0) and salt concentrations (0.05, 0.1, 0.2, 0.35 and 0.5 mol/l) for three types of salt (NaCl, Na2SO4 and (NH4)2SO4) on the solubility of egg white protein and density of egg white, at room temperature (25 °C) was studied. The results showed that the solubility of egg white protein was influenced by pH as well as concentration and type of salt present in the medium. Protein solubility increased with increase in pH, with higher solubility showed at pH 9.0 and lower solubility at pH 4.6. This behavior was verified for all the salts analysed. At acid pH (pH 3.0), it was observed the tendency of solubility elevation on the increase of the saline concentration, due to the salting-in effect. The density increased with increase in the salt concentration.
Keywords: Density; Egg white; Functional properties; Protein; Solubility